Keterampilan Kolaborasi Menggunakan Model Pembelajaran Berbasis Proyek pada Mata Pelajaran Fisik - Sarita, Nur; Nurhayati, Nurhayati; Saifuddin, Kurniadi (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. This study aims to improve students' collaboration skills by applying a project-based learning model in physics subjects in class X SMA Negeri 1 Soppeng. This research is a Classroom Action Collaboration Research that aims to overcome the problems found in the classroom. The research subjects were students of class X.4 odd semester of the 2023/2024 school year totaling 36 students. The research was conducted in two cycles and at the end of each cycle a reflection was carried out on the actions taken. Data collection techniques in the study using observation sheets and documentation. The results showed that the average percentage of collaboration of students in cycle I was 68.18% and cycle II was 80.18%. There was an increase in percentage which proves that the project-based learning model can improve the collaboration skills of class X students at SMA Negeri 1 Soppeng in physics subjects. Keywords: Project-based learning model, collaboration skills, class action research